PENENTUAN FAKTOR BOLTZMANN PADA PELUMAS SAE 10W-30 MELALUI PENDEKATAN VISKOSITAS BOLA JATUH SECARA PRAKTIS - Masta, Ngia; Evendi, Eki; Wardani, Randi; Karmila, Resmi (EduFisika: Jurnal Pendidikan Fisika, 2026)
Statistical mechanics bridges macroscopic fluid properties with microscopic molecular dynamics, yet its experimental estimation remains a challenge in physics education. To overcome this learning obstacle, Boltzmann Factor estimation could be performed with a simple Hands-on approach, one of which is the viscosity of a falling ball. This study validates the falling ball thermo-viscosity method for estimating activation energy and Boltzmann Factor in the Francis wall-correction model to resolve the wall effect with narrow tube (λ = 0.69). It uniquely applies Federal Racing Matic SAE 10W-30 oil bridging macroscopic kinetics with statistical microscopic parameters. The experiment was conducted by dropping a marble into the fluid at a fixed distance with a temperature variation between 308 K – 328 K. Compensation for the wall effect of the tube was carried out through Francis correction. Reynolds number indicated deviation from Stokes’ regime, resulting in an apparent rather than true viscosity. From the plot of approximation viscosity vs invers temperature, Arrhenius Law extracted  value is 35.66 ± 6.35 kJ/mol. Meanwhile relative Boltzmann Factor were close to the industrial data. Pearson's r (0.97) and values of R2 (0.94) indicate high methodological validity. Despite geometric limitations causing ~25% deviation in viscosity, the temperature-dependent trend remains enabling accurate activation energy estimation and extraction of the relative Boltzmann factor. These results support the falling ball viscosity method as a simple alternative experimental approach for quantitatively visualizing the abstract theory of classical particle distributions.